“Esprit de B Corps”: The rapid increase in B Corp accreditations across UK hospitality companies — a viewpoint on their collective potential and a future research agenda - Mark Ashton; Viachaslau Filimonau (Research in Hospitality Management)
The rapid growth of B-Corp certified organisations in the UK hospitality sector calls for a better understanding of their potential to influence the supply and demand sides of the market. It also requires an outline of a dedicated research agenda which will inform the design and implementation of future studies concerned with the impact of the B-Corp certification on hospitality operations and strategies. This viewpoint reviews B Corp as an emerging trend in the United Kingdom’s hospitality sector. It discusses the collective potential of B Corps to disrupt the hospitality market and enable its progress towards more inclusive, resilient and environmentally sustainable business models and practices. The viewpoint proposes a research agenda underpinned by four perspectives which can inform the emerging academic and industry discourse on the policy, management and wider societal and environmental implications of the B-Corp movement in the hospitality sector of the UK and beyond.